Entrepreneurial Competencies of Accountancy, Business, and Management Students of Balayan Senior High Students - Generoso, Ronald (Generasi Sains Indonesia, 2024)
This paper evaluates the extent to which the Human Resource Management (HRM) practices can aid in engaging the employees within the service sector that has been termed as an atmosphere that is driven by its popularity to depend on human-to-human interaction and service quality. It also means that employee engagement serves as one of the most valuable determinants of the customer satisfaction and overall success of the organisation as it is dependent on it. The current paper draws on the emerging literature that examined the impact of such HRM practices as training, recognition, performance management, work life balance and career development processes on the psychological and emotional attachment of employees to their roles. This paper will address this literature by covering a gap of clearly and carefully establishing causal relationship between interventions in the HRM and the extent of engagement in a well-formed set of experimental and quasi experimental studies. By adopting a quasi-experimental, quantitative study design, 200 employees in the service industry were requested to fill in the structured questionnaires. The discussion analyses the overall discreet HRM initiatives advantages as to achieving the tangible benefits in terms of engagement to the employees and is likely to guide the HR practitioners and the organisations as to how they can enhance the more committed, pleasured and productive workforce to the growing service economy.